2019
DOI: 10.1096/fj.201901046r
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of a small molecule agonist of the relaxin receptor ML290 in liver fibrosis

Abstract: Fibrosis is an underlying cause of cirrhosis and hepatic failure resulting in end stage liver disease with limited pharmacological options. The beneficial effects of relaxin peptide treatment were demonstrated in clinically relevant animal models of liver fibrosis. However, the use of relaxin is problematic because of a short half‐life. The aim of this study was to test the therapeutic effects of recently identified small molecule agonists of the human relaxin receptor, relaxin family peptide receptor 1 (RXFP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Alternatively, small molecule agonists have proven to be an attractive alternative to therapies with peptide ligands due to improved stability and potential oral bioavailability. A high-throughput screening of small molecules successfully identified the first RXFP1 agonist, compound ML290, which has antifibrotic effects recently demonstrated in a mouse model of liver fibrosis (Kaftanovskaya et al 2019). Due to the structural similarities of RXFP1 and RXFP2, the same approach that was used for the selection and optimization of ML290 can be applied to identify a small molecule agonist that specifically targets RXFP2.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, small molecule agonists have proven to be an attractive alternative to therapies with peptide ligands due to improved stability and potential oral bioavailability. A high-throughput screening of small molecules successfully identified the first RXFP1 agonist, compound ML290, which has antifibrotic effects recently demonstrated in a mouse model of liver fibrosis (Kaftanovskaya et al 2019). Due to the structural similarities of RXFP1 and RXFP2, the same approach that was used for the selection and optimization of ML290 can be applied to identify a small molecule agonist that specifically targets RXFP2.…”
Section: Discussionmentioning
confidence: 99%
“…Organoids were constructed using a slight modification of previously published protocols. [ 22‐25 ] Cryopreserved primary human hepatocytes, kupffer cells, and hepatic stellate cells were purchased from TRL/Lonza. Human liver sinusoidal endothelial cells were purchased from ScienCell and expanded for three passages according to the manufacturer's instructions, before being cryopreserved in 5 × 10 5 aliquots.…”
Section: Methodsmentioning
confidence: 99%
“…Liver organoids have been fully characterized as previously published, and they show high viability over at least 28 days, produce urea, albumin and alpha1 antitrypsin, and P450 reductase, and show a primitive bilary system and metabolize diazepam for at least 28 days. [ 22‐25 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ML290 is a specific agonist for human RXFP1 and does not activate the rodent receptor ( Huang et al, 2015 ). In this study, we utilized a unique strain of mice generated in our laboratory with knock-in of the human RXFP1 ( Kaftanovskaya et al, 2019 ) to test the therapeutic efficacies of ML290 in vivo . A plethora of studies reported the anti-fibrotic role of relaxin ( Samuel et al, 2016 ), and we recently showed that ML290 replicates the protective functions of relaxin in a mouse model of liver fibrosis ( Kaftanovskaya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%